2021
DOI: 10.1016/j.ajoc.2021.101129
|View full text |Cite
|
Sign up to set email alerts
|

Macular hemorrhage after laser exposure and cannabinoid intake during a disco party

Abstract: Purpose To describe two cases of macular hemorrhage in young patients, both occurred after laser exposure and cannabinoid intake during a disco party. Observations Case 1: a 21-year-old man was evaluated at our Emergency Unit for sudden vision loss in the right eye (RE). Best-corrected visual acuity (BCVA) was count fingers in the RE and 20/20 in the left eye (LE). Fundus examination revealed a broad pre-retinal hemorrhage in macular region of RE, confirmed by optical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…[ 17 ] reported retinal hemorrhages and retinochoroidal coagulation spots in two patients who attended the same dance festival with an audience-scanning laser show. Similarly, Fossataro et al [ 20 ] reported two young cases of macular hemorrhage, both of which occurred after laser exposure and cannabinoid intake during the same disco party. Aras et al .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…[ 17 ] reported retinal hemorrhages and retinochoroidal coagulation spots in two patients who attended the same dance festival with an audience-scanning laser show. Similarly, Fossataro et al [ 20 ] reported two young cases of macular hemorrhage, both of which occurred after laser exposure and cannabinoid intake during the same disco party. Aras et al .…”
Section: Discussionmentioning
confidence: 91%
“…Though eye injuries are uncommon during public gatherings, a few such instances have been reported in the past; yet most of these have been limited to a single case or a handful of cases. [ 16 17 18 19 20 ] Here, we report the clinical presentation and outcomes from a series of 34 eyes that experienced laser-related eye injuries while attending the same religious festival during the same time. To the best of our knowledge, this is the largest series of laser-related eye injuries reported from a single public gathering.…”
mentioning
confidence: 99%